1986
DOI: 10.1021/jm00159a003
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of sodium (.beta.R*,.gamma.S*)-4-[[3-(4-acetyl-3-hydroxy-2-propylphenoxy)propyl]thio]-.gamma.-hydroxy-.beta.-methylbenzenebutanoate: a novel, selective, and orally active receptor antagonist of leukotriene D4

Abstract: 1573may occur in other drug-receptor systems. For example, opioid phenylmorphans and 3-phenyl-and 4-phenylpiperidines also form such pair^.^^^^"^ A possible molecular explanation for the opposite activity of enantiomers may be the delocalization of charge that occurs when amines are p r o t~n a t e d .~~ That is, rather than being concentrated on the ammonium hydrogen, the positive charge is spread over the adjacent C-N bonds so that the "back" of the N-H bond also contains significant positive charge. Thus, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Although the chromone residue has not been subjected to extensive SAR studies, in the development of Pranlukast ( 7 ) it was observed that replacement of the chromone by other bicyclic systems devoid of a ketone carbonyl group (e.g., benzodioxans, quinolines, benzofurans, or naphthalenes) resulted in significant decrease of activity . Since several other CysLT 1 antagonists also contain ketone carbonyl groups in this region, this moiety may be prone to specific interactions with the receptor. We therefore selected this carbonyl (restraint value 2) and the carbon atoms of the acidic moieties (restraint 100) as fitting points.…”
Section: Methodsmentioning
confidence: 99%
“…Although the chromone residue has not been subjected to extensive SAR studies, in the development of Pranlukast ( 7 ) it was observed that replacement of the chromone by other bicyclic systems devoid of a ketone carbonyl group (e.g., benzodioxans, quinolines, benzofurans, or naphthalenes) resulted in significant decrease of activity . Since several other CysLT 1 antagonists also contain ketone carbonyl groups in this region, this moiety may be prone to specific interactions with the receptor. We therefore selected this carbonyl (restraint value 2) and the carbon atoms of the acidic moieties (restraint 100) as fitting points.…”
Section: Methodsmentioning
confidence: 99%
“…This is best illustrated with the differences between L-649,923 and L-647,438. Both compounds showed similar intrinsic potency in in vitro studies [8,9]. However, the ketobutyric acid sidechain of L-647,438 can undergo facile t-oxidation and the corresponding acetic acid derivative is rapidly eliminated in the rat probably through conjugation.…”
Section: Resultsmentioning
confidence: 85%
“…Accordingly testing of compounds has been routinely carried out in animals pretreated with methysergide. Two novel orally active 5-1ipoxygenase inhibitors, L-615,919 and L-651,392 [7], and leukotriene D4-receptor antagonists, L-647,438 and L-649,923 [8,9], have been used to illustrate how the model may be used for studying the effects of compounds that modulate the action or production of leukotriene D4. These compounds were tested over a 20 month period using animals from the 13th to 16th generation of this line of rats.…”
Section: Resultsmentioning
confidence: 99%
“…The substances were diluted in 9 glitre-1 saline solution and added to organ baths to establish cumulative dose-response curves within the range of 0.01 nM-l00nM for LTD4 and 1 nM-IO pm for LTB4 and for the lipoxins. In selected experiments, tissues were pre-incubated for 30min at 37°C with defined concentrations of FPL 55712 (7-[3-(4-acetyl-3-hydroxy-2-propylphenoxy)2-hydroxypropoxy] -4-oxo-8-propyl-4H-1-benzopyran-2-carboxylic acid, Fisons), L 649923 (sodium(fi5*, yR*) -4 -(3 -(4-acetyly -3 -hydroxy-2 -propylphenoxy) propylthic)-y-hydroxy-,B-methylbenzene-butanoate, Merck Frosst), indomethacin (Sigma) or L 651392 (4 -bromo -2,7 -dimethoxy -3H -phenothiazin -3 -one, Merck Frosst) (Young et al, 1986) a 5-lipoxygenase inhibitor (Guindon et al, 1987), prior to the establishment of cumulative dose-response curves to leukotrienes and lipoxins. In separate experiments, parenchymal tissues were pre-incubated for 30 min at 37°C with a combination of 1O-M indomethacin and 10-5M mepyramine in the presence and absence of 10 -5M L651392.…”
Section: Methodsmentioning
confidence: 99%